Preparation and characterization of ion beam sputtered graphitic carbon nitride thin film. (2021) - Sharath, R.A.; Fang, F.; Trompetter, W.J.; Futter, J.; Kennedy, J.
Abstract: Ion beam sputtering is a versatile technique to create nanostructured thin films with precise control over process parameters. We report the properties of graphitic carbon nitride (g-C3 N4 ) thin films deposited by ion beam sputtering. Ion beam analysis methods including Rutherford Backscattering Spectrometry (RBS), Nuclear Reaction Analysis (NRA) and Particle Induced X-ray Emission (PIXE) were used for quantitative determination of composition, thickness, elemental depth profile and trace, major elements and impurities. It was found that by directly using compressed g-C3 N4 powders as the sputter target material and tuning the process parameters, g-C3 N4 thin films with well controlled deposition rate were obtained. Post-annealing above 250 °C under argon atmosphere for 30 min was needed to recrystallize the g-C3 N4 nanostructure. Our results suggest that ion beam sputtering technique is a promising method to obtain uniform and high-quality g-C3 N4 thin films.